Hubungan Minat Belajar dengan Hasil Belajar Menjahit Blus Kelas X Busana 1 di Smk Negeri 8 Surabaya - Febriyanti Dwi Anggraini; Peppy Mayasari; Imami Arum Tri Rahayu; Mita Yuniati (Journal on Education, 2024)
Studying and learning is an activity that will produce learning outcomes. One of the factors that influence learning outcomes is interest. The objectives of the research conducted at SMK Negeri 8 Surabaya were to: 1) measure the learning interest of class X Busana 1 students, 2) determine the learning outcomes of class Basic Sewing Class X Clothing 1, 3) Find out whether there is a relationship between interest in learning and the results of learning to sew blouses in the Basic Sewing Technique elements of class X Clothing 1 at SMK Negeri 8 Surabaya. The research conducted is included in the quantitative research category. The entire sample consisted of 32 Class X Clothing 1 students. The approach used for sample selection waspurposive sampling. Questionnaires and tests are two techniques for collecting data. The SPSS version 25 program is used in the correlation methodProduct Moment which has a significance level of 5%. The results of the study show that : 1) Class X Clothing 1 students have a moderate interest in learning with a percentage of 91% in the blouse sewing element; 2) Class X Clothing 1 students sewing blouses had learning outcomes in the incomplete category with a percentage of 53% or 17 students; 3) there is a relationship between interest in learning and the results of learning to sew blouses in class X Clothing 1 and gradesthemselves. (2-tailed) is 0.000, (0.000 < 0.05). Correlation valuePearson namely 0.615 > 0.349.